So you're considering introducing congestion charging? Here's what you need to know - Jonas Eliasson (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
The paper draws from already published material. In fact, a reader already familiar with the congestion charging literature will find few completely new findings or insights. The contribution of the paper is rather the selection of the most relevant, interesting, important and sometimes surprising facts, insights, findings, advice and conclusions for policymakers, out of a vast literature on congestion charging in general and Stockholm in particular.
Keywords: 330